KEEFEKTIFAN MODEL PEMBELAJARAN QUANTUM TEACHING TERHADAP KREATIFITAS DAN HASIL BELAJAR MATEMATIKA KELAS III SD - Wahyudha Eka Permana (Universitas Muhammadiyah Surakarta, 2016)
This research aims to know the effectiveness of of Quantum Teaching learning model in the learning process Mathematic in SDN Peterongan Semarang. This is quantitative research with pretest posttest design. Population in this research are all student of III grade in SD Negeri Peterongan Semarang which amount to 26 students by using sampling technique that is saturated sample. Based on result of research data analysis after getting treatment by using Quantum Teaching model obtained count = 8,122 t table = 1,706. Then the alternative hypothesis is accepted. This means that the results of the third grade students of SD Negeri Peterongan Semarang achieve KKM 60. While the creativity character of students on the post-test results obtained 2.616 ttabel = 1.706. This means that the creativity character of third grade students of SD Negeri Peterongan Semarang reaches the value with good criteria ≥ 70. The average score of student creativity character is 72,69 with good criterion. The calculation of pretest and posttest values is different, in pretest it gets an average score of 59.38 whereas in posttest the average score is 74.15. Based on this obtained thitung ttable that is 8,541 2,056. Therefore, it can be concluded that Quantum Teaching learning model can improve creativity and learning result of Mathematics of third grade students SDN Peterongan Semarang.